Effect of gestational weight gain on preeclampsia among underweight women: A single tertiary referral center study in Japanese women. Issue 5 (4th March 2022) - Kyozuka, Hyo; Jin, Toki; Fujimori, Mimori; Nomura, Shinji; Suzuki, Daisuke; Fukuda, Toma; Murata, Tsuyoshi; Yasuda, Shun; Yamaguchi, Akiko; Nomura, Yasuhisa; Fujimori, Keiya
Abstract: Aim: To examine the effect of weight gain during pregnancy on preeclampsia among women with a prepregnancy body mass index < 18.5 kg/m 2 . Methods: This retrospective cohort study included 479 Japanese women with singleton pregnancies and a prepregnancy body mass index < 18.5 kg/m 2, who gave birth between 2013 and 2019 at Ohta Nishinouchi Hospital. The study included 22 (18 with preeclampsia and four with gestational hypertension) and 457 patients with and without hypertensive disorders of pregnancy, respectively. Results: The prevalence of hypertensive disorders of pregnancy and preeclampsia was 4.6% and 3.8%, respectively. With weight gain during pregnancy (continuous variable) set as a reference, multiple logistic regression revealed that excessive weight gain during pregnancy increased the risk of preeclampsia (adjusted odds ratio: 1.13, 95% confidence interval: 1.00–1.28, p  < 0.05) and hypertensive disorders of pregnancy (adjusted odds ratio: 1.15, 95% confidence interval: 1.03–1.29, p  < 0.05). Based on receiver operating characteristic curve analyses (area under the curve 0.65, 95% confidence interval: 0.50–0.80; p  < 0.05), we determined the cutoff value of weight gain during pregnancy for the occurrence of preeclampsia among women with body mass index < 18.5 kg/m 2 to be 13.0 kg, with sensitivity and specificity of 0.50 and 0.78, respectively. Conclusion: This study indicates that excessive weight gain during pregnancy increases preeclampsia risk among underweight women and provides new recommendations for weight gain during pregnancy for such women. Further research regarding the pathogenesis of preeclampsia for underweight women is warranted.